Norma Jean, jumping bean - Cole, Joanna; Munsinger, Lynn (New York : Random House, 1987)
Norma Jean, whose love of jumping might be a bit excessive, stops her favorite activity after her friends complain, but participation in the school Olympics proves there is a time and place for jumping.
Keywords: Jumping -- Fiction; Kangaroos -- Fiction; Animals -- Fiction